The Personal Branding Strategy of Jerome Polin as a Mathematics Edu-tainer on TikTok - Chiqqo Fajarulloh; Abdul Jalil Hermawan (Indonesian Journal Publisher, 2026)
This study investigates the personal branding strategy implemented by Jerome Polin as a mathematics edutainer on TikTok. A qualitative descriptive approach was adopted, using Montoya and Valdehey’s personal branding theory as the analytical framework. The theory consists of three fundamental dimensions: You, Promise, and Relationship. The research data were obtained through observations of 15 TikTok videos published between October 2024 and October 2025, along with in-depth interviews conducted with three followers of the @jerompolin TikTok account. The findings demonstrate that Jerome Polin successfully applies the three dimensions of personal branding. The You dimension represents his identity as a content creator who integrates mathematical expertise with a friendly, engaging, and easy-to-follow communications style, allowing audiences to understand the material more effectively. The Promise dimension is reflected in his consistent presentation of mathematics educational content that is simple, well-organized, practical, and reliable. Meanwhile, the Relationship dimension is shown through his active engagement with followers and his warm, personal approach to communication, enabling him to establish meaningful and lasting relationship with his audience. Overall, the personal branding strategy adopted by Jerome Polin strengthens his reputation as a credible, approachable, and relevant mathematics educator on social media. This study concludes that the combination of professional competence, consistency in delivering messages, and continuous audience interaction serves as the primary foundation for developing a strong personal brand in the digital communication era.